The effects of thiamine pyrophosphate on ethanol induced optic nerve damage - Turgay Ucak; Yucel Karakurt; Gamze Tasli; Ferda Keskin Cimen; Erel Icel; Nezahat Kurt; Ibrahim Ahiskali; Halis Süleyman (BMC, 2019)
Abstract Background We aimed to determine the protective effects of thiamine pyrophosphate on ethanol induced optic neuropathy in an experimental model. Methods The rats were assigned into 4 groups, with 6 rats in each group as follows: healthy controls (HC group), only ethanol administered group (EtOH group), ethanol + thiamine pyrophosphate (20 mg/kg) administered group (TEt-20 group), and only thiamine pyrophosphate (20 mg/kg) (TPG group) administered group. To the rats in TEt-20 and TPG groups, 20 mg/kg thiamine pyrophosphate was administered via intraperitoneal route. To the rats in HC and EtOH groups, the same volume (0.5 ml) of distilled water as solvent was applied in the same manner. To the rats in TEt-20 and EtOH groups, one hour after application of thiamine pyrophosphate or distilled water, 32% ethanol with a dose of 5 g/kg was administered via oral gavage. This procedure was repeated once a day for 6 weeks. From the blood samples and tissues obtained from the rats, Malondialdehyde (MDA), reduced glutathione (GSH), interleukin 1 beta (IL-1β) and tumor necrosis factor alpha (TNF-α) levels were studied. Histopathological evaluations were performed to the optic nerve tissue. Results Serum and tissue IL-1β, TNF-α and MDA levels were the highest in EtOH group which were significantly lower in thiamine pyrophosphate administered group (TEt-20 group) (p: 0.001). Serum and tissue reduced GSH levels were the lowest in EtOH group which were also significantly higher in TEt-20 group (p:0.001). In histopathological evaluations, in EtOH group there was obvious destruction and edema with hemorrhage and dilated blood vessels which were not present in any other groups. Conclusions There was an apparent destruction in ethanol administered group in histopathological analyses with an augmented level of oxidative stress markers and all those alterations were prevented with concomitant thiamine pyrophosphate administration. These protective effects of thiamine pyrophosphate are extremely important in chronic ethanol consumption. Clinical studies are warranted to define the exact role of thiamine pyrophosphate in prevention of ethanol induced optic neuropathy.